Effect of fuel preheating on performance, emission and combustion characteristics of a diesel engine fuelled with Vateria indica methyl ester blends at various loads. (15th February 2022) - Kodate, Shankar Vitthal; Raju, Pragada Satyanarayana; Yadav, Ajay Kumar; Kumar, G.N.
Abstract: The present study examines the preheated (95 °C) and unheated (35 °C) Vateria indica methyl ester (VIME) blends by studying the engine performance, combustion, and emission characteristics at various loads. A single-cylinder, TV1 Kirloskar direct injection diesel engine is used to carry out the tests. Biodiesel produced from Dhupa fat through the transesterification process is used as a renewable fuel in a diesel engine. In this work, diesel (B0), VIME (B100), and two binary blends (B30 and B50) are used. VIME has a higher viscosity, higher density, and lower calorific value than diesel, resulting in lesser brake thermal efficiency (BTE) and higher brake specific energy consumption (BSEC). Due to high viscosity of the biodiesel, preheating of fuel is done before injecting into cylinder. Preheating reduces the viscosity, and enhances the atomization and vaporization of fuel, resulting in improved engine performance. For a given blend of VIME biodiesel and diesel, the preheated blend has better BTE, decreased BSEC and lesser CO and HC emissions, with a slight increment in NOX emission compared to the unheated blend. The preheated B30 blend has a BTE value of 30.3% which is close to the BTE value of 30.1% of unheated diesel at 100% load condition. CO, HC, and soot emissions are decreased by 16.2%, 34.4%, and 16.5%, respectively, for preheated B100 fuel compared to unheated B100, at full load. Highlights: The preheated VIME biodiesel (95 °C) shows similar viscosity as unheated diesel. In a diesel engine, preheating of VIME biodiesel leads to fine atomization. Engine performance, emission and combustion parameters are studied at various loads. Preheated fuel gives better engine performance and lesser CO, HC, and soot emissions. The BTE of preheated B30 at full load is close to the unheated diesel's BTE.